Development of Interactive Multimedia Assisted by Canva to Enhance Students' Critical Thinking in Learning at SDN Lesanpuro 1 - M. Zainuddin; Surayanah, Surayanah; Khotimah, Khusnul; Ramila, Audiza Asssyifa; Cholida, Nur; Rahyuni, Sri; Lestariningsih, Lestariningsih (Journal of Development Research, 2024)
Currently, students still struggle with critical thinking. In fact, this ability is very important to solve everyday problems. To overcome this, we can use exciting and interactive learning with the help of technology. Unfortunately, many teachers still use the old way of teaching so that students get bored quickly. Therefore, this study aims to create interesting and interactive learning media using Canva application so that students can be more trained in critical thinking. This research was conducted on grade IV students at SDN Lesanpuro 1 Malang City. The method used is development research (R&D) with the ASSURE model. Data collection techniques used observation, questionnaires, pre-test and post-test, and documentation. The data was analyzed to assess the validity, practicality, and effectiveness of the learning media in improving critical thinking. The findings indicated that the developed learning media was valid, practical, and effective in fostering students' critical thinking abilities. In addition, students also really like this learning media so that they become more motivated to learn.